Braveness As Self Defence Act Against Crime Reflected In The Crazies Movie (2010) Directed By Breck Eisner: A Psychoanalytic Approach - Setiyawan, Setiyawan, Drs. Abdillah Nugroho, M.Hum, Nur Hidayat Spd (2013)
The major problem of this study is how the braveness as Self defence is reflected in the major character's personality. The aim of this study is to analyze The Crazies Confidence Movie based on the structural element and the development of the personality of the major characters based on an psychoanalytic approach perspective. The study focuses on the major characters, namely David. The method of data collecting is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the Movie; while secondary data source is include books and other data that have relation with the research. Technique of the data collecting is taking note. The technique of data analysis is descriptive study. Based on the structural analysis, The Crazies wants to deliver a message that sometimes people do kindness to overcome the braveness as self defense. Based on an Psychoanalytic analysis, it is clearly that The Crazies describes the psychoanalytic approach phenomena in which the characters (David) of this Movie have different goals of life with different problems to be solved.